2014
DOI: 10.2298/vsp121221024k
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases 2, 7 and 9 in patients with colorectal cancer

Abstract: Immunohistochemical expression of MMPs is a useful indicator of the disease development and progression in patients with colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Several lines of evidence suggest that CAFs are potent initiators of angiogenesis because these cells promote the secretion of MMPs (angiogenic factors) from cancer cells. (19,20) We observed that the mRNA expression of MMP-7 was markedly enhanced (Suppl. Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Several lines of evidence suggest that CAFs are potent initiators of angiogenesis because these cells promote the secretion of MMPs (angiogenic factors) from cancer cells. (19,20) We observed that the mRNA expression of MMP-7 was markedly enhanced (Suppl. Fig.…”
Section: Resultsmentioning
confidence: 98%
“…STAT‐3 signaling induces MMP‐7 expression in PDA cells. Some studies have suggested that MMP‐7 and other MMPs are elevated in human CRC and regulate the angiogenic activity of VEGF in colorectal tissue to promote angiogenesis . Indeed, CAFs induce greater MMP‐7 expression than NFs or PFs can in cancer cells; FGF‐1/‐3 induced MMP‐7 expression both in vitro and in vivo , and inhibiting FGFR4 phosphorylation using PD173074 or FGFR4 silencing reduced MMP‐7 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated that regulation of MMP s secretion leads to the acceleration of tumor invasion [1619]. MMP -2 and MMP -9 promote the degradation of the extracellular matrix, proliferation [20–22], and invasion of colon cancer cells [2326]. We hypothesized that, in colon cancer cells, SCRN1 regulates the secretion of MMP s to promote cell proliferation and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring protein expression in the tissue of patients with CRC, Kostova et al (32) noticed that the expression of MMP-9 exhibited a positive correlation with the level of tumor invasion. By contrast, no correlation was detected in the present study between active MMP-2 and the level of tumor invasion.…”
Section: Discussionmentioning
confidence: 99%